2005
DOI: 10.1212/01.wnl.0000168910.48309.4a
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of restless legs syndrome in French adults

Abstract: Restless legs syndrome (RLS) occurred in 10% of women and 5% of men. RLS prevalence decreases after the age of 64. RLS is often underdiagnosed and few subjects receive recommended RLS drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
170
6
15

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(213 citation statements)
references
References 30 publications
22
170
6
15
Order By: Relevance
“…The current authors also found a 25% prevalence of restless legs syndrome in CPAP user patients with RES. This is significantly greater than the prevalence reported in the French general population [25]. In clinical cohorts, 30% of restless legs syndrome patients complain of EDS as assessed by an ESS score of .10 [26].…”
Section: Prevalence Of Resmentioning
confidence: 67%
“…The current authors also found a 25% prevalence of restless legs syndrome in CPAP user patients with RES. This is significantly greater than the prevalence reported in the French general population [25]. In clinical cohorts, 30% of restless legs syndrome patients complain of EDS as assessed by an ESS score of .10 [26].…”
Section: Prevalence Of Resmentioning
confidence: 67%
“…[3][4][5][6][7][8] RLS is either idiopathic or it occurs in association with many physical and mental conditions. [9][10][11][12] The severity varies widely, ranging from occurring only occasionally to frequently and severely with disruption of sleep.…”
mentioning
confidence: 99%
“…This proportion is slightly higher than the 25% percent prevalence reported by Nichols et al, 35 and is considerably higher than the rates of 7.2% and 9% reported in 2 general population surveys. 36,37 This discrepancy may reflect that, although relatively common, RLS is often not diagnosed by physicians. In one study from 6 countries, 81% of the 416 respondents with RLS symptoms reported discussing their symptoms with a primary care physician, but only 21 (6.2%) were given a diagnosis of RLS.…”
mentioning
confidence: 99%